Microbial community succession patterns and drivers of Luxiang-flavor Jiupei during long fermentation - Liu, Xiaogang; Ma, Dongna; Yang, Chen; Yin, Qianqian; Liu, Shuangping; Shen, Caihong; Mao, Jian (Frontiers in Microbiology, 2023)
Luxiang-flavor Baijiu is the mainstream of Baijiu production and consumption in China, and the microbial composition has a great influence on the flavor and quality of Baijiu. In this study, we combined multi-omics sequencing technology to explore the microbial composition, dynamics and metabolite changes of Luxiang-flavor Jiupei during long fermentation periods. The results showed that based on the interaction between environmental constraints and microorganisms, Jiupei microorganisms formed different ecological niches and functional differentiation, which led to the formation of Jiupei stable core microorganisms. The bacteria were mainly Lactobacillus and Acetobacter, and the fungi were mainly Kazachstani and Issatchenkia. Most bacteria were negatively correlated with temperature, alcohol and acidity, and for the fungi, starch content, reducing sugar content and temperature had the most significant effects on community succession. Macroproteomic analysis revealed that Lactobacillus jinshani had the highest relative content; microbial composition, growth changes and functions were more similar in the pre-fermentation period (0-18 days); microorganisms stabilized in the late fermentation period (24-220 days). The metabolome analysis revealed that the metabolites of the Jiupei changed rapidly from 18 to 32 days of fermentation, with a significant increase in the relative content of amino acids, peptides and analogues and a significant decrease in the relative content of sugars; the metabolites of the Jiupei changed slowly from 32 to 220 days of fermentation, with a stabilization of the content of amino acids, peptides and analogues. This work provides insights into the microbial succession and microbial drivers during the long-term fermentation of Jiupei, which have potential implications for optimizing production and improving the flavor of Baijiu.